Chest CT scan findings in World Trade Center workers. Issue 5 (3rd September 2019) - de la Hoz, Rafael E.; Weber, Jonathan; Xu, Dongming; Doucette, John T.; Liu, Xiaoyu; Carson, Deborah A.; Celedón, Juan C.
ABSTRACT: We examined the chest CT scans of 1, 453 WTC responders using the International Classification of High-resolution CT for Occupational and Environmental Respiratory Diseases. Univariate and bivariate analyses of potential work-related pleural abnormalities were performed with pre-WTC and WTC-related occupational exposure data, spirometry, demographics and quantitative CT measurements. Logistic regression was used to evaluate occupational predictors of those abnormalities. Chest CT scans were performed first at a median of 6.8 years after 9/11/2001. Pleural abnormalities were the most frequent (21.1%) across all occupational groups In multivariable analyses, significant pre-WTC occupational asbestos exposure, and work as laborer/cleaner were predictive of pleural abnormalities, with prevalence being highest for the Polish subgroup (n = 237) of our population. Continued occupational lung disease surveillance is warranted in this cohort.